Energy Conserving Lattice Boltzmann Models for Incompressible Flow Simulations (Communications in Computational Physics, 2020)
In this paper, we highlight the benefits resulting from imposing energy-conserving equilibria in entropic lattice Boltzmann models for isothermal flows. Theadvantages are documented through a series of numerical simulations, such as Taylor-Green vortices, cavity flow and flow past a sphere.